Identification and Characterization of Antimicrobial Peptides From Butterflies: An Integrated Bioinformatics and Experimental Study - Wang, Min; Zhou, Ziyue; Li, Simin; Zhu, Wei; Hu, Xianda (Frontiers in Microbiology, 2021)
Identification and Characterization of Antimicrobial Peptides from Butterflies: An Integrated Bioinformatics and Experimental Study